EFFECTS OF FOOD QUALITY, SERVICE QUALITY, PRICE, ENVIRONMENT, AND LOCATION TOWARDS CUSTOMER LOYALTY OF INDONESIA’S LOCAL FAST FOOD INDUSTRY - Sunaryo, Indryati (J@ti Undip : Jurnal Teknik Industri, 2019)
This study aims to measure and analyze the effect of several restaurant-related quality attributes toward customer loyalty with a mediating effect from customer satisfaction in the local fast-food industry in Indonesia. The nature of local fast-food industry is different compared to its global counterpart, so a new perspective has to be taken into account. Based on literature review of previous studies, the quality attributes that are selected for this study are food quality, service quality, environment, price, and location. Data in this study were collected from the responses of 461 participants and analyzed using Structural Equation Model (SEM). The SEM result shows that only price and location significantly affect customer loyalty through customer satisfaction. When customer satisfaction is removed and restaurant-related quality attributes is directly tested towards customer loyalty, only price and food quality significantly affect customer loyalty. Both with and without mediating effect from customer satisfaction, price keeps influencing customer loyalty. This result is against the majority of fast-food customer loyalty studies which usually emphasize on food or service quality as the main factor that influences customer loyalty and customer satisfaction.